Catalan Nationalism - Balcells, Albert. author. aut Link
XVIII, 226 p.
Keywords: This book, the first study of Catalan nationalism to appear in English, outlines the history of Catalonia, showing how the national and cultural identity of the region persisted despite persecution. This provides the necessary background for the analysis of the contemporary political and cultural situation in Catalonia in the wider context of the European Union.